The effectiveness of Unasur to the solution of political crisis in South America (2008-2013) - Quispe Robles, Javier Luciano (2017)
In the last decade South American has been the scenario of different political crises with considerable repercussions on regional stability. In that sense, the participation of regional institutions for the solution of political crises has become increasingly important. This article seeks to understand the scope and limitations of the Union of South American Nations (Unasur) for the solution of political crises in the region. Since its origins, Unasur has sought to play an important role in efforts to maintain political stability in South America. However, while in some cases its participation has been effective; in others it has been limited or insufficient. One question remains: What determines Unasur's effectiveness in resolving political crises? This article argues that it is important to observe the interests and actions of the South American States in the face of each crisis to understand the scope of Unasur as an institution that guarantees regional stability. Adopting tools derived from structural realism, it can be observed that Unasur can be effective as long as there is agreement between the regional powers. However, if it does not exist, the action of Unasur is limited and insufficient.This article will analyze the crises of Bolivia in 2008; Ecuador in 2010; the diplomatic conflict between Colombia and Venezuela in 2009-2010; Paraguay in 2012; and Venezuela in 2013. Thus, the article not only studies the effectiveness of Unasur as a regional body, but also discusses the possibilities and limitations of political integration in South America in view of the distribution of power and competition among regional powers.